Buvatina iremella sp. n. (Lepidoptera: Oecophoridae) from the southern Ural Mountains - Junnilainen, Jari; Nupponen, Kari (Entomologica Fennica, 1999)
Buvatina iremella sp. n. is described from the southern Ural Mountains. Three male specimens were collected by light from an old taiga forest in the end of June. The main characteristics of the new taxon are long saccus and aedeagus in the male genitalia. The systematic position of the species is shortly discussed.